Development of Interactive Digital Teaching Materials on The Theme of Tagesablauf Based on Articulate Storyline 3 with The Integration of German Culture as An Independent Learning Resource for Grade XI Students - Widjanarko, Lydia Cita; Julaikah, Dwi Imroatu (LATERNE, 2026)
This study aims to describe the development process and to determine the feasibility of interactive digital teaching materials based on Articulate Storyline 3 on the theme of Tagesablauf for 11th-grade German language learning in senior high school. This study is motivated by students’ difficulties in understanding basic materials that are abstract and lack contextual relevance, which leads to low learning motivation. The method used in this study is the ADDIE model, limited to the stages of analysis, design, and development. The validation subjects in this study involved a lecturer from the Undergraduate Program in Educational Technology at Universitas Negeri Surabaya as a media expert and a German language teacher at SMA St. Maria Surabaya as a subject-matter expert. The results show that the development process of the teaching materials was carried out through needs analysis, interface and content design, and the development of a product based on Articulate Storyline 3 containing die Uhrzeit material integrated with the use of articles (der, die, das) in the context of daily activities. The teaching materials are also complemented by Kulturblick content presenting aspects of German culture, as well as interactive exercises such as true/false, fill-in-the-blank, and drag-and-drop activities. The feasibility test results indicate that the teaching materials achieved a score of 80% for the content aspect and 96% for the media aspect, thus falling into the “feasible to highly feasible” category. Therefore, these teaching materials can be used as an interactive learning medium as well as a self-study resource for 11th-grade students.